3D Shape Measurement That Uses the Laser Light - Takai, Toshihisa (DENKI-SEIKO, 2008)
Non-contact three-dimensional measurement has been widely applied recently. This is because the measurement enabled a new type of shop-floor production (monodukuri) which increased the productivity and made it possible to measure free-form surface which had been impossible in the past. Triangulation 3D scanner is an equipment that realizes the three-dimensional measurement. Especially, the laser probe method is less subject to the color and the luster of the object, so it is a very worthwhile way to measure industrial instrumentation. Details of the scanner are described in this article.